The relationship between the countries' performances at the major sport events with their performance at the Olympic Games - Bahman Asgarı; Shahab Bahramı (Selcuk University, 2015)
The purpose of this study was study of Relationship between countries performance at multi-sport events and world championships with their performance at Olympic Game. The population of all the countries in the Olympic Games medals have been won that their number is equal 1166 (excluding repeat). Based on Morgan table, samples were selected equal 321. Information was collected from multiple sites such as international federations, Olympic Continental Councils and international Olympic committee. Also, for analyzing used descriptive and inferential statistics (Kolmogorov-Smirnov test and Spearman correlation coefficient) by SPSS software and significant level pâ‰¤0.05. The results showed that there is positive and significantly relationship between the number of medals of gold, silver, bronze and total medals won by countries at former Olympic Games, world championships, Asian and Pan-American Games with the number of Medals of gold, silver, bronze and total medals won at upcoming Olympic Games, However, there is not significantly relationship between the number of medals of gold, silver, bronze and total medals won at all-African Games with the number of medals of gold, silver, bronze and total medals won at Olympic Games.